Controlled degradation of polycaprolactone-based micropillar arrays. (6th March 2023) - Geoghegan, Niamh; O'Loughlin, Mark; Delaney, Colm; Rochfort, Keith D.; Kennedy, Meabh; Kolagatla, Srikanth; Podhorska, Lucia; Rodriguez, Brian J.; Florea, Larisa; Kelleher, Susan M.
Abstract : Herein we demonstrate the fabrication and controlled degradation of arrays of polycaprolactone-based micropillars, achieved through the combination of direct laser writing and nanoimprint lithography. Abstract : Herein we demonstrate the fabrication of arrays of micropillars, achieved through the combination of direct laser writing and nanoimprint lithography. By combining two diacrylate monomers, polycaprolactone dimethacrylate (PCLDMA) and 1, 6-hexanediol diacrylate (HDDA), two copolymer formulations that, owing to the varying ratios of the hydrolysable ester functionalities present in the polycaprolactone moiety, can be degraded in the presence of base in a controllable manner. As such, the degradation of the micropillars can be tuned over several days as a function of PCLDMA concentration within the copolymer formulations, and the topography greatly varied over a short space of time, as visualised using scanning electron microscopy and atomic force microscopy. Crosslinked neat HDDA was used as a control material, demonstrating that the presence of the PCL was responsible for the ability of the microstructures to degrade in the controlled manner. In addition, the mass loss of the crosslinked materials was minimal, demonstrating the degradation of microstructured surfaces without loss of bulk properties was possible. Moreover, the compatibility of these crosslinked materials with mammalian cells was explored. The influence of both indirect and direct contact of the materials with A549 cells was assessed by profiling indices reflective of cytotoxicity such as morphology, adhesion, metabolic activity, oxidative balance, and release of injury markers. No significant changes in the aforementioned profile were observed in the cells cultured under these conditions for up to 72 h, with the cell–material interaction suggesting these materials may have potential in microfabrication contexts towards biomedical application purposes.